IDEAL TIME FOR THE EXECUTION OF ASYNCHRONOUS CLASS IN LANGUAGE LEARNING T&L SESSION - Nurazwani Binti Zakaria,; Zeety Kartini Binti Abdul Hamid,; Nurul Imtiaz Binti Abdul Gani,; Marzalina Binti Mansor,; Juwati Binti Abdullah, (Journal of Islamic, Social, Economics and Development, 2023)
This study seeks to determine the duration of learning focus by gender that influences the optimal time in asynchronous classes for language learning. This implies that this study will clarify the difference between male and female students' time or focus during a single online learning session. The primary impetus is the realisation that students must identify the optimal time for Teaching and Learning (T&L) sessions to be more effective, particularly in language learning. An effective T&L procedure will undoubtedly result in increased student achievement. A critical review of previous studies revealed that there is no research discussing the optimal time or hours for online language learning. The majority of previous research has concentrated on the motivation, positive effects, and impact of online teaching. In online language learning, the quantity of time or hours required to determine a student's focus is never taken into account. Therefore, based on the analysis of questionnaires from 91 students, the optimal duration for online language learning by gender has been determined. Results on the optimal time for online language learning by gender revealed no significant difference in the best time to maintain focus between male and female UUM students.